MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA GUNUNG BUNDER I, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Nurhasan, Abdul Khodir; Faiz, Marcelino (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Gunung Bunder 1 village is located in Pamijahan District, Bogor Regency, West Java Province. This village has sufficient natural resources to support the development and socioeconomic well-being of its community. In this community service program, a plan is in place to provide access to sharia financing for Micro, Small, and Medium Enterprises (MSMEs) and farmers in Desa Gunung Bunder 1. The activities begin with identifying problems among MSME and farmer stakeholders, followed by data collection. The collected data and information are then processed to develop a solution plan. This plan includes providing training to enhance the knowledge and understanding of MSMEs and the agricultural sector regarding sharia financing, as well as improving the awareness and confidence of MSME and farmer stakeholders in Desa Gunung Bunder 1.